Climate Change Vulnerability Assessment in Informal Urban Settlements - Gurung, Pujan; Pokhrel, Rajib (Journal of Engineering and Sciences, 2025)
International and national organizations have focused on two major policy responses to address climate change. They focus on reducing the emission of greenhouse gases to slow down the rate of change and increasing the coping capacity of countries, sectors and communities. Furthermore, rapid and unplanned urbanization, poverty, unemployment, lack of alternate housing opportunities, social and economic exclusion of migrating rural poor and the need to be located close to urban resources and opportunities, have resulted in the increasing number of urban poor population with informal slum settlements. Therefore, accessing the climate change vulnerability of the informal urban slum settlements of Suklagandaki Municipality was the main objective of this research. It explored Intergovernmental Panel on Climate Change (IPCC) vulnerability index by surveying 89 households from four different places in Suklagandaki Municipality. The Livelihood Vulnerability Index - Intergovernmental Panel on Climate Change (LVI-IPCC) included eleven major dimensions under exposure, sensitivity and adaptive capacity condition. The analysis was based on indices constructed from thirty-four indicators. Results indicated that Maalebagar-8 was most vulnerable and Ward-2 area was least vulnerable with the value in the range of moderate vulnerability. Both National Adaptation Plan of Action (NAPA) and Local Adaptation Plan of Action (LAPA) are oriented toward addressing climate hazards and overlook sociopolitical and underlying causes of vulnerability and lack a process to identify and address the most vulnerable communities especially the urban slum. The outcome of this study will be helpful for developing climate change and disaster management policies and programs for similar urban settlements in the future.